GEOMORPHOLOGY, SEDIMENTOLOGY AND GEOCHEMISTRY IN THE MARINE AREA BETWEEN SIFNOS AND KIMOLOS ISLANDS, GREECE - Karageorgis, A.P.; Ioakim, Chr.; Rousakis, G.; Sakellariou, D.; Vougioukalakis, G.; Panagiotopoulos, I.P.; Zimianitis, E.; Koutsopoulou, E.; Kanellopoulos, Th.; Papatrechas, Ch.; Georgiou, P.; Xirokostas, N.; et al. (Bulletin of the Geological Society of Greece, 2016)
An extensive oceanographic survey was conducted in the marine area between Kimolos and Sifnos Islands, a rather poorly-studied sector of the Aegean Sea, in order to gain better understanding of submarine geomorphological features and associated sediment provenance. Multi-beam bathymetry and surface sediment sampling with a box corer were carried out on board R/V Aegaeo, followed by grain-size analysis, XRD and XRF measurements. A large circular depression was identified north of Kimolos reaching a water depth of 743 m, filled with fine grained sediments. Surface sediment distribution is characterized by gradual decrease in grain-size from silty sand to silt in a S-N direction. The mineralogical composition comprises calcite, Mgcalcite, aragonite, dolomite, quartz, K feldspars, plagioclase, amphiboles and clay minerals. Major sediment provinces identified were: (i) the shallow sector proximal to Kimolos, characterized by higher contents in Si, Al, K, Rb and Ba; (ii) the deep area west of Sifnos, including the large depression, characterized by higher contents in Fe, Ti, Na, Mg, S, Cr, Cu, Ni, V, Zn; and (iii) the south passage between Kimolos and Sifnos, which exhibits higher Ca, S, and Sr contents. Manganese enrichment was observed in and around the bathymetric depression, where Mn oxides act efficiently as scavengers of a suite of metals.